Reflection-Based Academic Supervision: The Principal’s Effort to Improve Learning Quality at SDN 02 Sidorejo - Anita Ema Ridiyawati; Senowarsito; Maryanto (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to describe how reflective-based academic supervision is implemented by the principal as an effort to improve learning quality at SDN 02 Sidorejo. Using a qualitative descriptive case study design, data were collected through in-depth interviews, participatory observation, and documentation. The findings reveal that academic supervision is carried out through a reflective cycle consisting of planning, implementation, evaluation, and follow-up. In the planning stage, teachers are involved in identifying instructional problems and determining improvement priorities. During implementation, supervision is conducted using clinical steps: pre-observation discussions, classroom observation, and reflective conferencing. The follow-up phase includes mentoring, lesson study, peer coaching, and reflective journals. The results show improvements in teacher pedagogical competence, including lesson planning, classroom management, and instructional media use. Student learning outcomes also increase, demonstrating positive instructional impact. Reflective academic supervision positions the principal as a coach and collaborator, fostering a culture of continuous improvement and professional growth.